Psychometric Properties of the Chinese Version of the Brief Borderline Symptom List in Undergraduate Students and Clinical Patients - Yang, Huihui; Lei, Xiaoxia; Zhong, Mingtian; Zhou, Qi; Ling, Yu; Jungkunz, Martin; Yi, Jinyao (Frontiers in Psychology, 2018)
The brief version of the Borderline Symptom List (BSL-23) is a self-rated scale developed from the initial 95-item version of Borderline Symptom List (BSL-95). The current study aimed to evaluate the psychometric properties of the Chinese version of the BSL-23. A total of 570 undergraduate students and 323 clinical patients completed the BSL-23, the borderline subscale of the Personality Diagnostic Questionnaire (PDQ-4+), the Center for Epidemiologic Studies Depression Scale (CES-D), the Barrat Impulsiveness Scale, 11th version (BIS-11), the Childhood Trauma Questionnaire (CTQ) and the Attachment Style Questionnaire (ASQ). A Confirmatory Factor Analysis (CFA) was conducted to test the one-factor structure of the BSL-23. Cronbach’s alpha, Omega coefficient, Split-Half coefficient, Mean Inter-Item Correlation (MIC) and test-retest reliability were also measured. The correlations between the BSL-23 and other psychological variables were used to assess criterion-related validity and convergent validity. Participants who scored ≥ 5 on the borderline subscale of the PDQ-4+ were placed into the borderline personality disorder (BPD) screening-positive group, while the others were placed into the screening-negative group. Independent sample t-tests were performed to examine the differences in BSL-23 scores between the BPD screening-positive group and the BPD screening-negative group. The CFA results supported the one-factor structure of the BSL-23 in both samples. The internal consistency was high both in the undergraduate sample (Cronbach’s α = 0.93, Omega = 0.95, Split-Half coefficient = 0.89, MIC = 0.38) and the clinical sample (Cronbach’s α = 0.97, Omega = 0.97, Split-Half coefficient = 0.96, MIC = 0.56). The test-retest reliability within two weeks was 0.62. The BSL-23 displayed moderate to high correlations with the PDQ-4+-Borderline subscale, the CES-D, the BIS-11, the CTQ and the ASQ (r = 0.35 - 0.70). In addition, the BSL-23 discriminated between the BPD screening-positive and the BPD screening-negative participants, and also between the patient sample and undergraduate sample. In conclusion, the Chinese version of the BSL-23 has satisfactory psychometric properties to assess BPD symptoms.